(untitled) (UNIZIK Journal of STM Education, 2025)
This study investigated into the effect of the use of number line system game in teaching and learning of arithmetic to primary four pupils in Ihiala L.G.A. of Anambra State. Two research questions and two hypotheses guided the study. The design of the study was a quasi – experimental research design. The population was seven hundred and sixty-five (765) primary four pupils in Ihiala LGA of Anambra State. Two primary schools and two intact classes were selected using simple random sampling techniques by balloting method out of 23 primary schools in Ihiala L.G.A..The Number Line System Game Achievement Test (NLSGAT) which consist of twenty (20) multiple choice questions was used for data collection. The experimental group was taught arithmetic using the number line system game while the control group was taught the same content using the conventional method. The research questions formulated were analyzed using mean and standard deviation while the two hypotheses were tested using Z-test. Findings to this study revealed that; pupils taught arithmetic using the number line system game performed better than their counterparts taught without using the number line system game. The result also revealed that there was no significant difference between the mean achievement scores of male and female pupils taught with number line system game. Based on the findings of the study, it was recommended among others that the school administrators, stakeholders and government should encourage the use of number line system game in the teaching of arithmetic to primary school pupils in Anambra State.